Binding of ISRIB reveals a regulatory site in the nucleotide exchange factor eIF2B - Zyryanova, Alisa F.; Weis, Félix; Faille, Alexandre; Abo Alard, Akeel; Crespillo-Casado, Ana; Sekine, Yusuke; Harding, Heather P.; Allen, Felicity; Parts, Leopold; Fromont, Christoph; Fischer, Peter M.; Warren, Alan J.; et al. (American Association for the Advancement of Science, 2018)
The integrated stress response (ISR) is a conserved translational and transcriptional program affecting metabolism, memory, and immunity. The ISR is mediated by stress-induced phosphorylation of eukaryotic translation initiation factor 2α (eIF2α) that attenuates the guanine nucleotide exchange factor eIF2B. A chemical inhibitor of the ISR, ISRIB, reverses the attenuation of eIF2B by phosphorylated eIF2α, protecting mice from neurodegeneration and traumatic brain injury. We describe a 4.1-angstrom-resolution cryo–electron microscopy structure of human eIF2B with an ISRIB molecule bound at the interface between the β and δ regulatory subunits. Mutagenesis of residues lining this pocket altered the hierarchical cellular response to ISRIB analogs in vivo and ISRIB binding in vitro. Our findings point to a site in eIF2B that can be exploited by ISRIB to regulate translation.